NON-COMPETITION CLAUSES IN COMMERCIAL CONTRACTS - MIHAELA IRINA IONESCU (Challenges of the Knowledge Society, 2011)
We begin with an analysis of areas where rivalry between economic agents can not show (any act of competition committed in this area drawing the liability of the author), we will then analyze competition in relations between the trader and servant or other employees and continue with the analysis of the legal ban on competition in the limited liability companies and joint stock companies. So, the relevant provisions of Law 31/1990 are reviewed, views of legal doctrine and practice of judicial rulings on the nature and purpose of the relevant provisions referred to, their scope, applicability of statutory prohibition against competition in the profile activity of the company, the prohibition in the liquidation phase, procedural methods which can cover damage caused to the creditor’s violated rights, as well as statute of limitations for the right to action and prescription.